Cerebral venous thrombosis complicated by hemorrhagic infarction in pregnancy: Case report - Balduz, Metin; Kapan, Oktay; Özdemir, Hasan Hüseyin; Da?li, Iklimya N.; Demir, Caner F. (Turkish Society of Cerebrovascular Diseases, 2011)
Cerebral sinus thrombosis (CST), often occurring in young and middle age population is one of the cerebrovascular diseases. It can become more frequent during pregnancy. Low-molecular-weight heparin (LMWH) offers the option of treatment for cerebral sinus thrombosis. A 24-year-old 10 weeks pregnant woman presented with headache and seizure. LMWH was administered initially. Consciousness developed during clinical follow-up. In the meantime MRI, hemorrhagic infarctions were detected in left temporal lobe and in left thalamus. MRA showed thrombus within the left transverse sinus extending into the sigmoid sinus. Maintenance therapy regulated with reduction of LWMH. Lamotrigine was started for the treatment of seizures. Resolution of hemorrhage was detected in the following imagings. She was discharged home to continue with Low weight molecular heparin treatment. Herein a case of complicated cerebrovasculer disease in pregnancy is presented and literature is reviewed.
Gebeli?kte hemoraji?k i?nfarkt i?le kompli?ke serebral venöz tromboz: Olgu sunumu
Keywords: Cerebral venous thrombosis; Hemorrhagic infarction; Pregnancy